Insights Into Type I and III Interferons in Asthma and Exacerbations - Rich, Helen E.; Antos, Danielle; Melton, Natalie R.; Alcorn, John F.; Manni, Michelle L. (Frontiers in Immunology, 2020)
Asthma is a highly prevalent, chronic respiratory disease that impacts millions of people worldwide and causes thousands of deaths every year. Asthmatics display different phenotypes with distinct genetic components, environmental causes, and immunopathologic signatures, and are broadly characterized into type 2-high or type 2-low (non-type 2) endotypes by linking clinical characteristics, steroid responsiveness, and molecular pathways. Regardless of asthma severity and adequate disease management, patients may experience acute exacerbations of symptoms and a loss of disease control, often triggered by respiratory infections. The interferon (IFN) family represents a group of cytokines that play a central role in the protection against and exacerbation of various infections and pathologies, including asthma. Type I and III IFNs in particular play an indispensable role in the host immune system to fight off pathogens, which seems to be altered in both pediatric and adult asthmatics. Impaired IFN production leaves asthmatics susceptible to infection and with uncontrolled type 2 immunity, promotes airway hyperresponsiveness (AHR) and inflammation which can lead to asthma exacerbations. However, IFN deficiency is not observed in all asthmatics, and alterations in IFN expression may be independent of type 2 immunity. In this review, we discuss the link between type I and III IFNs and asthma both in general and in specific contexts, including during viral infection, co-infection, and bacterial/fungal infection. We also highlight several studies which examine the potential role for type I and III IFNs as asthma-related therapies.